FIBR3DEmul-an open-access simulation solution for 3D printing processes of FDM machines with 3+actuated axes - Faria, Carlos (2020)
This paper introduces a virtual emulator software for additive manufacturing (AM) processes based on filament deposition, the FIBR3DEmul. The presented software is capable of reading and parsing a G-Code file (ISO/DIN 66025), and realistically emulating a custom-designed 5-axis printer or a standard 3-axis Cartesian printer. The FIBR3DEmul was designed and implemented in two separate applications for reusability and scalability. First, the G-Code Interpreter is responsible for parsing the g-code script, controlling the flow of its execution, and notifying the user about detected printer-printer or printer-workpiece collisions. The second application involves the robotics simulator tool V-Rep. A custom plugin was implemented to mediate the communication with the Interpreter application, to generate the tool trajectories, to emulate the extrusion process, and to handle motion execution and collision detection. The process of designing and implementing a custom-printer control and motion execution in these two software is described. The performance of the virtual 5-axis printer was compared with the real machine in terms of position and velocity profiles. Results show a tight match between virtual and real printer-generated plots. The presented solution can also be extrapolated to CNC machines or WHASPs. The FIBR3DEmul source code is publicly available.